Efektivitas Metode Audiolingual dalam Meningkatkan Hasil Belajar Bahasa Arab Santriwati Kelas VII Ponpes Mutiara Qur’an Wonogiri - Zahrah Ghufrani (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
The purpose of this classroom action research project is to find out how well seventh-grade female students at Mutiara Qur'an Islamic Boarding School in Wonogiri learn Arabic with the use of the audiolingual approach. By emphasizing active listening and pronunciation, the audiolingual approach makes it easier for students to comprehend and communicate in Arabic. Twelve female seventh-graders at Mutiara Qur'an Islamic Boarding School participated in the researcher's qualitative study in order to gather the research findings. The study was conducted in two cycles to enhance Arabic language learning. Planning, action, observation, and reflection are the four components of each cycle in the Kurt Lewin model. Tests, observations, and interviews were the methods utilized to get the data. The proportion of learning mastery and descriptive analysis were used to examine the collected data. The study's findings show that the audiolingual approach is successful in raising female students' Arabic language learning outcomes.